Photosynthetic response of Quercus ilex L. plants grown on compost and exposed to increasing photon flux densities and elevated CO 2 (Photosynthetica, 2005)
Quercus ilex plants grown on two different substrates, sand soil (C) and compost (CG), were exposed to photosynthetic photon flux densities (PPFD) at 390 and 800 µmol(CO2) mol -1 (C390 and C800). At C800 both C and CG plants showed a significant increase of net photosynthetic rate (PN) and electron transport rate (ETR) in response to PPFD increase as compared to C390. In addition, at C800 lower non-photochemical quenching (NPQ) values were observed. The differences between C390 and C800 were related to PPFD. The higher PN and ETR and the lower dissipative processes found in CG plants at both CO2 concentrations as compared to C plants suggest that substrate influences significantly photosynthetic response of Q. ilex plants. Moreover, short-term exposures at elevated CO2 decreased nitrate photo-assimilation in leaves independently from substrate of growth.